Transformational school leadership in wetland environments: Prospects for Indonesian education - Setiawan, Muhammad Andri; Aslamiah (Jurnal Inspirasi Pendidikan, 2026)
This study aims to analyze and map the characteristics of school leadership in wetland environments and to evaluate the prospects for implementing an ecological–social leadership model in Indonesia, particularly in South Kalimantan province. Using a systematic–descriptive literature review, the research synthesized twenty peer-reviewed articles published between 2019 and 2025 that examined school leadership practices in ecologically extreme regions across Asia, Africa, and South America. The data were collected through a structured matrix and analyzed thematically to identify patterns of leadership adaptation in flood-prone and geographically isolated contexts. The results show that effective school leadership in wetland environments requires a multidimensional capacity that integrates transformational, instructional, and sustainable–ecological leadership. Transformational leadership strengthens teacher motivation and collective vision; instructional leadership enhances teaching quality and contextual learning; while sustainable leadership ensures school resilience through ecological awareness and community collaboration. The findings further indicate that leadership effectiveness is influenced by internal factors, such as competence, adaptability, and communication, and external factors, including policy support, organizational culture, and local wisdom. The study concludes that an ecological–social leadership framework, grounded in Banjar cultural values such as gawi sabumi (collective cooperation) and environmental stewardship, provides a viable model for improving educational leadership in wetland-based schools. This integrative model bridges global leadership theory with Indonesia’s socio-ecological realities, contributing to the pursuit of resilient, equitable, and sustainable education. Future research is recommended to validate this framework through empirical studies and policy implementation in other ecologically vulnerable regions.